Coordinative Alignment of Chiral Molecules to Control over the Chirality Transfer in Spontaneous Resolution and Asymmetric Catalysis. Issue 1 (December 2017) - Xia, Zhengqiang; Jing, Xu; He, Cheng; Wang, Xiaoge; Duan, Chunying
Abstract The production and availability of enantiomerically pure compounds that spurred the development of chiral technologies and materials are very important to the fine chemicals and pharmaceutical industries. By coordinative alignment of enantiopure guests in the metal‒organic frameworks, we reported an approach to control over the chirality of homochiral crystallization and asymmetric transformation. Synthesized by achiral triphenylamine derivatives, the chirality of silver frameworks was determined by the encapsulated enantiopure azomethine ylides, from which clear interaction patterns were observed to explore the chiral induction principles. With the changing of addition sequence of substrates, the enantioselectivity of asymmetric cycloaddition was controlled to verify the determinant on the chirality of the bulky MOF materials. The economical chirality amplification that merges a series of complicated self-inductions, bulk homochiral crystallization and enantioselective catalysis opens new avenues for enantiopure chemical synthesis and provides a promising path for the directional design and development of homochiral materials.